2017
DOI: 10.1002/cm.21346
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the effects of lattice defects on microtubule breaking and healing

Abstract: Microtubule reorganization often results from the loss of polymer induced through breakage or active destruction by energy-using enzymes. Pre-existing defects in the microtubule lattice likely lower structural integrity and aid filament destruction. Using large-scale molecular simulations, we model diverse microtubule fragments under forces generated at specific positions to locally crush the filament. We show that lattices with 2% defects are crushed and severed by forces three times smaller than defect-free … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
63
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(76 citation statements)
references
References 60 publications
10
63
3
Order By: Relevance
“…In particular, molecular dynamics simulations can apply pulling or pushing forces at particular locations along the microtubule lattice to determine the work required to destroy the lattice. 6164 In these works, it is clear that the intramolecular bonds between dimers are the weak points in the lattice, and they come apart before dimers are unraveled. 64 These studies are complimented by several experimental studies of the structure of filaments during and after forced destruction by depolymerizing enzymes or severing enzymes.…”
Section: Feedback and Control In The Assembly Of Tubulin Into Microtumentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, molecular dynamics simulations can apply pulling or pushing forces at particular locations along the microtubule lattice to determine the work required to destroy the lattice. 6164 In these works, it is clear that the intramolecular bonds between dimers are the weak points in the lattice, and they come apart before dimers are unraveled. 64 These studies are complimented by several experimental studies of the structure of filaments during and after forced destruction by depolymerizing enzymes or severing enzymes.…”
Section: Feedback and Control In The Assembly Of Tubulin Into Microtumentioning
confidence: 99%
“…6164 In these works, it is clear that the intramolecular bonds between dimers are the weak points in the lattice, and they come apart before dimers are unraveled. 64 These studies are complimented by several experimental studies of the structure of filaments during and after forced destruction by depolymerizing enzymes or severing enzymes. 6567 Other studies have used atomic force microscopy (AFM) techniques to specifically push on microtubules.…”
Section: Feedback and Control In The Assembly Of Tubulin Into Microtumentioning
confidence: 99%
“…In addition to these structural studies, molecular dynamics simulations have suggested that it would be easier to remove a dimer by pushing into the lattice, rather than pulling to unravel a dimer (Barsegov et al, ; Jiang, Bailey, et al, ; Theisen, Desai, Volski, & Dima, ). Such computational results are additional evidence that the unfoldase mechanism is less likely than a wedging or pushing mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Several groups, including our own, have noted that katanin has the ability to depolymerize microtubules in addition to severing them (Díaz‐Valencia et al, ; McNally & Vale, ; Zhang et al, ). This activity is important when regulating microtubule length, particularly at the cortex in interphase cells and kinetochore fibers in mitosis (Jiang, Bailey, Burke, Ross, & Dima, ; Jiang, Rezabkova, et al, ; McNally, Audhya, Oegema, & McNally, ; Zhang et al, ; Zhang, Rogers, Buster, & Sharp, ). We have shown that katanin can depolymerize taxol‐stabilized microtubules in an ATP‐dependent manner (Díaz‐Valencia et al, ; Zhang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…the Regular (REG) model, which represents the GDP type lattice, and the All Homogenous model (AHM), which mimics the GMPCPP type lattice [Kononova et al, 2014, Jiang et al, 2017, Szatkowski et al, 2019, as described in the Methods section. Here we examined the unfoldase mechanism where the MT severing enzyme removes dimers through pulling on the CTT(s) of the tubulin dimer.…”
Section: Pathways For Microtubule Breaking By Pulling On One Subunitmentioning
confidence: 99%